EPIDEMIOLOGY OF TRACK & FIELD INJURIES: A ONE YEAR EXPERIENCE IN ATHLETIC SCHOOLS - Apostolos TH Stergioulas; Alexandra D Tripolitsioti; George Kipreos; Anastasios Tyflidis (Termedia Publishing House, 2012)
The purpose of this study was to record injuries in track & field events that were sustained by students who attended the athletic schools during a one-year period. From September 2009 to May 2010, the researchers observed 2045 students (883 males and 1163 females), who were participating in track and field events at the mentioned schools. During the study period 150 injuries were recorded, which accounted for 13.3% of all injuries sustained by students. Most of the injuries (34%) according to the diagnosis were sprains and strains and occurred during the months of February, December and January. A large percentage of the injuries (45.4%) were sustained by students who attended the Athletic Schools, which operated in the urban region. Students who attended the second class sustained more injuries than the other classes (first and third). Students who were practising or competing on a tartan playing surface were more likely to sustain an injury. Knee and ankle were the most frequent anatomical sites in which injuries (43.9%) occurred. Additionally, 80.0% of injuries occurred in students who were practising or competing in running events. No statistical differences were observed in all above mentioned parameters amongst male and female students. Physical education (P.E.) teachers should place more emphasis on prevention measures. These measures should include proper supervision of students during training, warming up and cooling down sessions with stretching techniques. By following these suggestions students will compete in a safe and healthy environment.